Exposing 010 Active Facets by Multiple‐Layer Oriented Stacking Nanosheets for High‐Performance Capacitive Sodium‐Ion Oxide Cathode. Issue 40 (24th August 2018) - Xiao, Yao; Wang, Peng‐Fei; Yin, Ya‐Xia; Zhu, Yan‐Fang; Niu, Yu‐Bin; Zhang, Xu‐Dong; Zhang, Jienan; Yu, Xiqian; Guo, Xiao‐Dong; Zhong, Ben‐He; Guo, Yu‐Guo
Abstract: As one of the most promising cathodes for rechargeable sodium‐ion batteries (SIBs), O3‐type layered transition metal oxides commonly suffer from inevitably complicated phase transitions and sluggish kinetics. Here, a Na[Li0.05 Ni0.3 Mn0.5 Cu0.1 Mg0.05 ]O2 cathode material with the exposed 010 active facets by multiple‐layer oriented stacking nanosheets is presented. Owing to reasonable geometrical structure design and chemical substitution, the electrode delivers outstanding rate performance (71.8 mAh g −1 and 16.9 kW kg −1 at 50C), remarkable cycling stability (91.9% capacity retention after 600 cycles at 5C), and excellent compatibility with hard carbon anode. Based on the combined analyses of cyclic voltammograms, ex situ X‐ray absorption spectroscopy, and operando X‐ray diffraction, the reaction mechanisms behind the superior electrochemical performance are clearly articulated. Surprisingly, Ni 2+ /Ni 3+ and Cu 2+ /Cu 3+ redox couples are simultaneously involved in the charge compensation with a highly reversible O3–P3 phase transition during charge/discharge process and the Na + storage is governed by a capacitive mechanism via quantitative kinetics analysis. This optimal bifunctional regulation strategy may offer new insights into the rational design of high‐performance cathode materials for SIBs. Abstract : An O3‐type Na[Li0.05 Ni0.3 Mn0.5 Cu0.1 Mg0.05 ]O2 cathode material with exposed 010 active facets by multiple‐layer oriented stacking nanosheets is successfully constructed via reasonable structure design and chemical substitution. An optimal bifunctional regulation is demonstrated to be an efficient strategy to restrain the unfavorable multiphase transformation and greatly improve Na + transport kinetics resulting in excellent performance for sodium‐ion batteries.